2015
DOI: 10.1016/j.conb.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar damage impairs internal predictions for sensory and motor function

Abstract: The cerebellum is connected to cerebral areas that subserve a range of sensory and motor functions. In this review, we summarize new literature demonstrating deficits in visual perception, proprioception, motor control, and motor learning performance following cerebellar damage. In particular, we highlight novel results that together suggest a general role of the cerebellum in estimating and predicting movement dynamics of the body and environmental stimuli. These findings agree with the hypothesized role of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…On the ASD side, studies have shown a reduction in purkinje cell numbers (Bailey et al, 1998;Ritvo et al, 1986) and a reduction in volume of the cerebellar vermis (Hashimoto et al, 1995;Murakami, Courchesne, Press, YeungCourchesne, & Hesselink, 1989;Scott, Schumann, Goodlin-Jones, & Amaral, 2009) and on the sensorimotor control side, it is well established that the cerebellum is critical for postural control, sensory integration and motor learning (for a review see Therrien & Bastian, 2015). While little is known about the role of the cerebellum in ASD individuals' postural control, a recent study assessed the role of the cerebellum in ASD and TD children's ability to learn a simple reaching task using visual and proprioceptive feedback (Marko et al, 2015).…”
Section: Postural Control In Autism Spectrum Disorder 16mentioning
confidence: 99%
“…On the ASD side, studies have shown a reduction in purkinje cell numbers (Bailey et al, 1998;Ritvo et al, 1986) and a reduction in volume of the cerebellar vermis (Hashimoto et al, 1995;Murakami, Courchesne, Press, YeungCourchesne, & Hesselink, 1989;Scott, Schumann, Goodlin-Jones, & Amaral, 2009) and on the sensorimotor control side, it is well established that the cerebellum is critical for postural control, sensory integration and motor learning (for a review see Therrien & Bastian, 2015). While little is known about the role of the cerebellum in ASD individuals' postural control, a recent study assessed the role of the cerebellum in ASD and TD children's ability to learn a simple reaching task using visual and proprioceptive feedback (Marko et al, 2015).…”
Section: Postural Control In Autism Spectrum Disorder 16mentioning
confidence: 99%
“…[30][31][32] This system has important connections with the cerebellum, which modulates multiple sensory inputs and plays a fundamental role in postural control by managing vestibulo-spinal reflexes and contributing to motor learning, perception, postural control, and orientation. 33,34 In the light of this, we believe that the SMIT may engage the vestibular system, cerebellum, and their downstream pathways. Training on the walking trail in the SMIT protocol appeared to be one of the most effective factors at play because this exercise included the use of various multisensory approaches, such as motor imagery, auditory cues, and multisystem integration.…”
Section: Sensory Motor Perceptual Integration Activitiesmentioning
confidence: 98%
“…Several studies have explored the existence of specific structures and the involvement in learning and functioning of internal models [61][62][63].…”
Section: Computational Approaches To the Motor Systemmentioning
confidence: 99%
“…Learning with endpoint feedback may rely more heavily on updating of feedforward models. The finding that cerebellar patients can adapt to a gradual visual rotation when cursor feedback is provided may reflect an ability to use compensatory online feedback corrections to improve reach accuracy [63].…”
Section: Computational Approaches To the Motor Systemmentioning
confidence: 99%